Study on the anti-biofilm mechanism of 1,8-cineole against Fusarium solani species complex - Zhang, Yu; Wang, Yiming; Zhao, Xinghong; Liu, Lu; Xing, Rui; Song, Xu; Zou, Yuanfeng; Li, Lixia; Wan, Hongping; Jia, Renyong; Yin, Lizi; Liang, Xiaoxia; et al. (Frontiers in Pharmacology, 2022)
Fungi-infections are mostly due to fungi in an adhering, biofilm-mode of growth and not due to planktonically growing, suspended-fungi. 1, 8-cineole is a natural product, which has been shown to possess antifungal effect. However, the anti-biofilm effect and mechanism of 1,8-cineole against Fusarium solani species complex has not reported previously. In this study, we found that 1,8-cineole has a good antimicrobial activity against F. solani with an MIC value of 50 μL/mL. Notably, 1,8-cineole showed good anti-biofilm formation activity against F. solani via inhibiting cell adhesion, hypha formation and decreasing the secretion of extracellular matrix at the concentration of ≥ 6.25 μL/mL. In addition, transcriptome sequencing analysis results showed that F. solani species complex genes related to ECM, protein synthesis and energy metabolism were down-expressed in the biofilms formation process treated with 1,8-cineole. In conclusion, these results show that 1,8-cineole has good anti-biofilm formation activity against F.solani species complex, and it exerts its anti-biofilm formation activity by downregulating of ergosterol biosynthetic genes, inhibiting adhesion, hindering the synthesis of ECM and interfering mitochondrial activity. This study suggests that 1,8-cineole is a promising anti-biofilm agent against F. solani species complex.